Family activism : immigrant struggles and the politics of noncitizenship - Pallares, Amalia, 1965- (Latinidad: transnational cultures in the United States., 2014)
"Drawing upon the idea of the "impossible activism" of undocumented immigrants, Amalia Pallares argues that those without legal status defy this "impossible" context by relying on the politicization of the family to challenge justice within contemporary immigration law. The culmination of a seven-year-long ethnography of undocumented immigrants and their families in Chicago, as well as national immigrant politics, Family Activism examines the ways in which the family has become politically significant"--